2000
DOI: 10.1029/2000jc900020
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and formation of the mesothermal structure (temperature inversions) in the North Pacific subarctic region

Abstract: Abstract. The distribution and formation of mesothermal structure (temperature inversions) in the North Pacific subarctic region are investigated through analysis of climatological hydrographic data. It is suggested that the heat and salt that maintain the mesothermal water and thus the halocline in the density range of 26.7-27.2cr0 are transported as a crossgyre flow from the transition domain just east of Japan, where the waters are influenced by the subtropical gyre water mass, to the eastern subarctic regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 13 publications
7
57
0
6
Order By: Relevance
“…In addition, relatively strong temperature inversions (>0.5°C) were observed between 160°E and 174°E. Temperature inversions are often apparent in the subarctic North Pacific (Ueno & Yasuda 2000, supporting the conclusion that the stations between 160°E and 174°E were located in the subarctic region. The present results revealed that in the surface layer, temperature was higher and chl.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, relatively strong temperature inversions (>0.5°C) were observed between 160°E and 174°E. Temperature inversions are often apparent in the subarctic North Pacific (Ueno & Yasuda 2000, supporting the conclusion that the stations between 160°E and 174°E were located in the subarctic region. The present results revealed that in the surface layer, temperature was higher and chl.…”
Section: Discussionsupporting
confidence: 58%
“…In the northern part of the KOC region, the 4 °C isotherm at 100 m depth (Favorite et al 1976) traces the southern boundary of the SAC well in the western and central portions of the North Pacific. This isotherm is the formal proxy of the southern limit of the "pure" subarctic stratification with a subsurface temperature minimum underlain by a temperature maximum (Belkin et al 2002), which is termed as the Subarctic Front (SAF) by Ueno and Yasuda (2000) and Yasuda (2003). 4 Further, recent studies based on satellite observations have identified two remarkable quasi-stationary jets in the SAFZ immediately south of the SAC [Isoguchi et al 2006;J1 and J2 in Figs.…”
Section: Kuroshio-oyashio Confluence Regionmentioning
confidence: 99%
“…SAB is the subarctic boundary. The front associated with the SAC is indicated as SAF here based on Ueno and Yasuda (2000) and Yasuda (2003) gradient, along-front flow speed, volume transport, frontal depth from the surface, and eddy kinetic energy (EKE) at the surface. These metrics provide the information on the momentum field associated with fronts.…”
mentioning
confidence: 99%
“…We obtained a decadal time series by combining data from the two stations, because the duration of sampling at each individual station data was not sufficient. Typically, in this region the minimum temperature (T min ) in the water column is associated with the remnant of the mixed layer water in the preceding winter and occurs at about 26.5σ θ (∼ 100 m), and the maximum temperature occurs at about 27.1σ θ (∼ 370 m) (e.g., Ueno and Yasuda, 2000;Osafune and Yasuda, 2006). Each year, the surface mixed layer reached its maximum depth from mid-March to early April (Fig.…”
Section: Data and Analysesmentioning
confidence: 99%
“…1), so occasionally no T min water is observed because of the northward migration of subtropical water (Tsurushima et al, 2002). Because this migrated subtropical water enters the south edge of western subarctic gyre and passes eastward (Ueno and Yasuda, 2000), we did not use observation data if no T min layer could be identified. This indicates the combined K2 and KNOT data in this study does not include the subtropical water and is not obviously different in hydrography.…”
Section: Data and Analysesmentioning
confidence: 99%